AB0264 Fatty Liver Index Predicts Glucose Metabolism Disturbance in Inflammatory Arthritis Patients. (15th July 2016) - Tripolino, C.; Ursini, F.; Bruno, C.; Nicolosi, K.; Naty, S.; Grembiale, R.D.
Abstract : Background: Several studies reported an increased prevalence of nonalcoholic fatty liver disease (NAFLD) in subjects with rheumatic diseases [1]. NAFLD can be evaluated non-invasively and reliably by magnetic resonance spectroscopy, computed tomography and ultrasound. However, these methods are time consuming or associate with high costs. Thus, alternative estimates of NAFLD based on routine risk factors and serum biomarkers have been proposed [2]. Interestingly, these surrogate indices associate with insulin resistance and risk of type 2 diabetes in the general population [3]. To date, no data are available about a possible association between surrogate indices of NAFLD and glucose metabolism disturbance in the setting of inflammatory arthritis. Objectives: To analyze the relationship between sierological markers of liver fat accumulation and 2-hours plasma glucose concentration (2hPG) in a population of rheumatic disease subjects undergoing an oral glucose tolerance test (OGTT). Methods: For our aim, we recruited 45 subjects diagnosed with inflammatory arthritis (rheumatoid arthritis, RA; psoriatic arthritis, PsA; undifferentiated spondiloarthritis, uSpa). Exclusion criteria were: current diabetes, severe renal and hepatic disease. After overnight fasting, OGTT was performed by oral administration of a standard dose of 75 g anhydrous glucose dissolved in water. Plasma glucose levels were measured in a fasting state and again two hours after its administration. Other laboratory analyses included: lipids, complete blood count, erythrocyte sedimentation rate (ESR), high sensitivity C-Reactive Protein (hsCRP), serum alanine transaminase (ALT), aspartate transaminase (AST) and and gamma-glutamyltransferase (GGT). The liver fat score (LFS), the hepatic steatosis index (HSI) and fatty liver index (FLI) were employed as serum NAFLD indices as previously described [2]. Pearson's or Spearman's correlation analyses were used as appropriate to test the associations between continuous variables. Not normally distributed variables were log-transformed before analysis. Results: 20 AR, 15 PsA and 10 uSpa composed our sample. Of these 16 were males and 29 were females. The mean age was 54±9.1. According to the OGTT results: 31 subjects were classified as NGT, 9 had IGT and 5 had diabetes. In simple correlation analyses, Ln2hPG significantly correlated with Age (r=0.48, p=0.001), BMI (r=0.44, p<0.01), HSI (r=0.43, p<0.01), LFS (r=0.37, p=0.01) and FLI (r=0.54, p<0.001). After controlling for BMI and age only FLI associated with 2hPG. Conclusions: Our data demonstrate an association between 2hPG and NAFLD surrogate indices in a population of inflammatory arthritis patients. Among these FLI seems better associate with glucose metabolism disturbance. References: Abraham S, Begum S, Isenberg D. Hepatic manifestations of autoimmune rheumatic diseases. Ann Rheum Dis. 2004;63:123–129. Kahl S, Straßburger K, Nowotny B, et al. Comparison of liver fat indices for the diagnosis of hepatic steatosis and insulin resistance. PLoS One. 2014;9:e94059. Finucane FM, Sharp SJ, Hatunic M, et al. Liver fat accumulation is associated with reduced hepatic insulin extraction and beta cell dysfunction in healthy older individuals. Diabetol Metab Syndr. 2014;6:43. Acknowledgement: None Disclosure of Interest: None declared